Envisioning Incentives for Improving University Governance: A Ghanaian Perspective - Bernard Bekuni Boawei Bingab; Joseph Ato Forson; Oscar Siema Mmbali; Theresa Yaaba Baah-Ennumh; Joshua-Luther Ndoye Upoalkpajor (International School for Social and Business Studies, 2016)
The incentive to strengthen university governance system has three implications: (1) improving the quality of the university education system, and thus providing students and the general public value for money, (2) enhancing the utilization of resources invested in university education, and (3) contributing significantly to the formation of human capital, quality of public leadership, and best services to the society. However, there are limited studies on how this can be realized in Ghana. This is a qualitative study seeking to explore the following questions: What is needed to ensure desirable university governance? And how can it be achieved? In-depth interviews and documentary research were used to collect data from twenty-three participants. The study examines key governance issues such as funding, accountability, infrastructure, trust, and regulation. The study contextually contributes to the literature on university governance and management by bringing to the fore the incentives needed to enhance it for a better output to meet the development needs of the Ghanaian economy and the African continent with similar challenges as a whole.